2002
DOI: 10.1159/000063898
|View full text |Cite
|
Sign up to set email alerts
|

Papulonodular Lichenoid and Pseudolymphomatous Reaction at the Injection Site of Hepatitis B Virus Vaccination

Abstract: Immunization with the hepatitis B virus (HBV) is effective and safe with an estimated incidence of adverse reactions, either local or systemic, of less than 0.1%. Cutaneous side effects are rare and include lichen planus (LP) and lichenoid reactions. We report the case of a 21-year-old female, in whom a persistent, papulonodular lesion developed at the site of the injection, 6 weeks after the second dose of the HBV. Histological examination revealed lichenoid and pseudolymphomatous features. In addition, sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…Nineteen cases of vaccine-induced B-cell CLH have been reported [3,4,5,6,7,8,9,10] including 11 cases following hepatitis B vaccination [3,4,8,10]. The others concerning vaccines were early summer meningo-encephalitis [4] in 2 cases, tetanus in 2 cases [4,5], hepatitis A [8] in 1 case, influenza [4] in 1 case and diphtheria tetanus poliomyelitis in 1 case [6].…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen cases of vaccine-induced B-cell CLH have been reported [3,4,5,6,7,8,9,10] including 11 cases following hepatitis B vaccination [3,4,8,10]. The others concerning vaccines were early summer meningo-encephalitis [4] in 2 cases, tetanus in 2 cases [4,5], hepatitis A [8] in 1 case, influenza [4] in 1 case and diphtheria tetanus poliomyelitis in 1 case [6].…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous pseudolymphomas may represent exaggerated reactions to diverse external stimuli, including drugs (6,9). The drug may not be the provocative agent per se, but may promote an aberrant immune response to an antigen that may be the drug itself or some other stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…7 Persistent non-neoplastic skin reactions have been reported following vaccinations, but are uncommon. 8,9 In one of the first articles on persistent vaccination site reactions, Orell reported fifteen cases of granulomatous subcutaneous nodular lesions associated with influenza vaccinations, which were attributed to fine-grained aluminum oxide particles used as adjuvants. Guinea pig studies revealed similar granulomatous reactions to fine-grained aluminum oxide adsorbed influenza vaccines.…”
Section: Discussionmentioning
confidence: 99%